Explaining Organizational Export Performance by Single and Combined International Business Competencies. (11th February 2018) - Birru, Worku Tuffa; Runhaar, Piety; Zaalberg, Ruud; Lans, Thomas; Mulder, Martin
Abstract : This study explores relationships between export performance and international business competencies (international orientation, export market orientation and international entrepreneurial orientation), and interactions between the competencies. Data from on‐site structured interviews with 159 owners and managers of exporting firms from different economic sectors show direct relationships between the competencies and export performance. However, analyses of the effects of interactions between the competencies and export performance show mixed results. The findings suggest developing the identified competencies to increase export performance, but if this would be exclusively based on the direct relationships between the competencies and export performance, results may be suboptimal.